Relaxation Analysis of LixNiO2 and Lix(NCA)O2 in the Deeply Lithium Extracted Region (x ≤ 0.12). Issue 7 (1st January 2017) - Tamura, Akihiro; Takai, Shigeomi; Yabutsuka, Takeshi; Yao, Takeshi
Abstract : Structural relaxation has been investigated on Li x NiO2 and Li x (Ni0.933 Co0.031 Al0.036 )O2 after the electrochemical lithium extraction to x ≤ 0.12. These relaxation analyses have been carried out using X-ray diffraction coupled with the Rietveld analysis assuming two phases (H2 and H3) co-existence with R 3 ¯ m symmetry. For all the compositions of Li x NiO2, mole fraction of H3 phase decreases with the relaxation time accompanied by the reduction of c -axis, while H2 phase retains c -length almost constant. Therefore, H3 phase excessively formed at the lithium extraction process partly transforms into the H2 phase during the relaxation. Although the similar relaxation phenomena reducing the mole fraction of H3 phase have been observed for Li x (Ni0.933 Co0.031 Al0.036 )O2, difference in c -length between the H2 and H3 phases is much smaller, which would facilitate the phase change to improve the battery performance utilizing such a higher potential region.